Correlation of histopathological results and tomographic findings in patients with liver lesions suspicious for malignancy.: Correlación del resultado histopatológico y hallazgos tomográficos en pacientes con lesiones hepáticas sospechosas de malignidad. - Valencia Montiel, Luis Pablo (2024)
Introduction. Liver cancer is the seventh most common neoplasm worldwide and the second cause of mortality directly associated with cancer. In Mexico it has an incidence of 3.9% in the entire population. Although computed tomography (CT) is the imaging study of choice, the final diagnosis is established with the anatomopathological study of the lesion. Objective. Correlate the tomographic findings with the histopathological result in patients with liver lesions with suspicion of malignancy, who underwent USG-guided biopsy. Methods. Descriptive, correlation, retrolective, homodemographic and single-center study. The study period was from September 2021 to February 2022. Patients older than 18 years with liver lesions suspicious of malignancy were selected and underwent Computed Axial Tomography and ultrasound-guided biopsy. Shapiro Wilk tests (for normality) were used and chi-square was used for an analysis of association of categorical variables. Results. Twenty-four patients were included, who underwent Tomography and lesion biopsy, finding an average size of lesions of 2.39cm. The results of the correlation between the tomographic diagnosis and the definitive histopathological diagnosis did not have statistical significance p=0.069. Conclusion. No significant correlation was found between the histopathological study and tomographic findings in liver lesions suggestive of malignancy.